Enhanced TAPS Software with Flipped Classroom Approach - Low, Min Chi; Lee, Chen Kang; Sidhu, Manjit Singh; Lim, Seng Poh; Hasan, Zaimah; Lim, Seng Chee (Multidisciplinary Applied Research and Innovation, 2022)
This research focus on the invention and development of enhanced Technology Assisted Problem Solving (TAPS) software integrated with the flipped classroom approach to enhance the visualization and problem solving in engineering. The enhanced TAPS software, which incorporates digital media technologies and new pedagogical concepts, was designed according to the blended learning settings. This software consists of interactive environment embedded with 2-D and 3-D animation. Flipped classroom, one of the models of blended learning, continues to be one of the popular learning pedagogies in tertiary education. Flipped classroom encourage the active learning environment by promoting the students’ participation in classroom activities and outside classroom interaction. In engineering education, one of the most common challenges that students encounter is having difficulty in visualize the engineering concept. These concepts typically entail dynamic motions and complex computations, especially in the z-axis. The engineering problem that are given to these students typically need to be addressed by using the relevant formulas, and doing so may lead to a series of working steps before the final answer can be obtained. The learning software for engineering that is now available on the market is incapable of integrate the problem solving and visualization module with flipped classroom approach. The findings from the empirical data indicated that the software an encouraging impact on the learning outcomes of engineering student. Students of mechanical engineering could benefit from using the enhanced TAPS software since it could increase their learning interest and improve their visualization capacity, which would ultimately contribute to the addressing of engineering problems in accordance to the trends of engineering education 4.0.